Induction of measles virus hemagglutinin in a persistently infected, nonvirogenic line of cells (BGM/MV). - Flanagan, T D (1976)
BGM/MV cells carry measles virus antigens and nucleocapsid-like structures in their cytoplasm. There is no infectious virus demonstrable, and measles virus-induced cell surface changes detectable by hemadsorption (HAD) are absent. Treatment of cells with actinomycin D or cycloheximide or enucleation of cells with cytochalasin B induced surface changes in that the cells became HAD positive. 6-Azauridine treatment of cells did not inhibit the induction of HAD, suggesting that RNA synthesis was not required. Cycloheximide treatment of cells induced by enucleation inhibited the development of HAD, suggesting a requirement for protein synthesis.